Cooperativa-escola: metodologia para a constru????o de uma cultura escolar cooperativa? - Belezia, Eva Chow (2006)
The objective of this study is to systematize the experiences acquired from the organization and implementation of Cooperative-Schools of Students at the state agricultural technical schools of the Centro Estadual de Educa????o Tecnol??gica Paula Souza, and to focus on the influence the Cooperatives had in the education and production programs of the technical courses in the farming area. This work is based on research of existing documentation which provided the time-line of the establishment of the agricultural technical education in Brazil and in the State of S??o Paulo, as well as that of cooperativism and cooperative schools. This research serves as the basis for the case study presented here. By the very nature of the study s objective, a cooperative school formed by the students of the agricultural technical schools can only provide an in depth understanding of its educational and productive dimensions if the live elements of the objective, that is, the students, professors and school administrators, are taken into consideration. The proposal of cooperative-school of students has an innovative character in the school management because it breaks the centralized power and hierarchy of the traditional school system. To determine these dimensions we used questionnaires distributed to teachers and students. In order to supplement the information from the questionnaires and to obtain personalized perceptions, we carried out Focus Group studies. Our conclusion is that a Cooperative-School is a consolidated enterprise in the school; it is the site for the practice of management and an instrument for educational methodology, adopted primarily by the teachers in the technical areas. It is also, with greater emphasis, the factor to dynamize the administrative-productive process of the farm where the school is located, and the management of the student residence in the agricultural technical school. In addition, the Cooperative-School constitutes the facilitating element for the participation of the students who, in this model, have the chance to offer their opinion and to contribute for decision-making in this productive-educational process.